Microorganismos patógenos causantes de infecciones nosocomiales y su incidencia en la estancia hospitalaria de los pacientes del Hospital Regional Isidro Ayora Loja. - Vásquez Poma, María Antonieta (2016)
The documentary studies around the world that nosocomial infections are a major cause of morbi-mortality, not only extend the stay of the patient but also contribute to increased costs. This study was conducted with the aim of identifying microorganisms that cause nosocomial infections and its impact on hospital stay in the General Hospital Isidro Ayora, Loja during 2015. A retrospective and descriptive study was conducted by reviewing medical records of a total of 165 patients who meet the inclusion criteria. According to the results of the frequency nosocomial infections was 1.7%, men and women with a prevalence of 50% each, the most affected age group was between 66-95 years with 43%. Infection was the most frequent infection of skin and soft tissue with a prevalence of 40%. The most frequently isolated microorganism was Escherichia coli with 17%. Nosocomial pneumonia and urinary tract infections causes a stay between 7-20 days more with 49% and 87% respectively; Infections of skin and soft tissue like cause osteomyelitis stay 21-30 days with 46%. Finally the service where the highest frequency of nosocomial infections was found areade internal medicine with 38%. Key words: Nosocomial Infection, Hospital Stay.